Embracing Evaluative Thinking for Better Outcomes: Four NGO Case Studies - CLEAR-AA; InterAction (My University, 2017)
This study would not exist without the contributions of many people. First, we must acknowledge the input of the international NGO participants at the Sub-Saharan Africa Practitioner Workshop on Evaluative Thinking and Evaluation Use, which was organized and facilitated by the African Evaluation Association (AfrEA), the Centre for Learning on Evaluation and Results for Anglophone Africa (CLEAR-AA), and InterAction in Accra, Ghana, December 10-12, 2013.
Keywords: Embracing Evaluation Thinking; NGO Case studies